Snail plays an oncogenic role in glioblastoma by promoting epithelial mesenchymal transition - Myung, Jae Kyung (e-Century Publishing Corporation, 2014)
Background: The factors affecting glioblastoma progression are of great clinical importance since dismal outcomes have been observed for glioblastoma patients. The Snail gene is known to coordinate the regulation of tumor progression in diverse tumors through induction of epithelial mesenchymal transition (EMT); however, its role in glioblastoma is still uncertain. Therefore, we aimed to further define its role in vitro. Methods and results: The small interfering RNA (siRNA) technique was employed to knock down Snail expression in three glioblastoma cell lines (KNS42, U87, and U373). Specific inhibition of Snail expression increased E-cadherin expression but decreased vimentin expression in all cell lines. In addition, inhibition of the expression of Snail significantly reduced the proliferation, viability, invasion, and migration of glioblastoma cells as well as increased the number of cells in the G1 phase. Conclusions: Knockdown of Snail suppresses the proliferation, viability, migration, and invasion of cells as well as inhibits cell cycle progression by promoting EMT induction. The findings suggest that expression of this gene facilitates glioblastoma progression. Therefore, these results indicate the clinical significance of Snail for use as a potential therapeutic target for glioblastoma.